Response of PLA material to 3D printing speeds: A comprehensive examination on mechanical properties and production quality - Kartal, Fuat; Kaptan, Arslan (European Mechanical Science, 2024)
This study investigates the impact of printing speed on the mechanical properties of parts produced through the fused deposition modeling (FDM) method using a three-dimensional (3D) printer. Tensile test specimens, fabricated with Polylactic Acid (PLA) material on an Ender 3 S1 3D printer, were subjected to varying printing speeds from 15 mm/s to 105 mm/s in 15 mm/s increments, maintaining a 100% infill rate. Detailed measurements of sample masses, hardness values, and surface roughness were conducted to assess the potential effects of printing speed on PLA’s mechanical properties. Porosity values were also calculated to evaluate internal structure homogeneity and void ratios. The results indicate that an increase in printing speed leads to a substantial reduction in production time. For instance, at a speed of 15 mm/s, the printing time was 119 minutes, decreasing to 15 minutes at 105 mm/s. As speed increased, there was a tendency for a decrease in sample masses, with a notable 12% reduction from 8.21 grams at 15 mm/s to 7.21 grams at 105 mm/s. While lower speeds (15 and 30 mm/s) exhibited higher Shore D hardness values, an overall decrease in hardness was observed with increasing speed. Surface roughness showed a proportional increase with printing speed; for example, at 0° angle, the roughness value increased from 0.8 at 15 mm/s to 1.9 at 105 mm/s. Moreover, tensile strength values decreased with higher printing speeds. For samples printed at 15 mm/s, the tensile strength was 60 MPa, decreasing to 44 MPa at 105 mm/s, representing a 27% reduction. These numerical findings underscore the significant influence of 3D printing speed on both production efficiency and the mechanical properties of the printed material.
Keywords: Material Design and Behaviors; Malzeme Tasarım ve Davranışları; Additive manufacturing; three dimensional printing; polylactic acid; printing speed; mechanical properties; surface roughness.